Sickness absence and permanent work disability in relation to upper- and lower-body pain and occupational mechanical and psychosocial exposures - Sommer, Tine Gjedde; Svendsen, Susanne Wulff; Frost, Poul (Scandinavian Journal of Work, Environment & Health, 2016)
' ' OBJECTIVE ': 'The aim of this study was to examine if combined pain (pain in the upper and lower body), high occupational mechanical exposures, and job strain predict sickness absence and permanent work disability, particularly if co-occurring. ' ' METHODS ': 'This longitudinal study was based on the musculoskeletal research database at the Danish Ramazzini Centre. We linked baseline information from 2001–2004 on musculoskeletal pain, job titles, and covariates with register information on sickness absence and permanent work disability. Mechanical and psychosocial exposure estimates were obtained from job exposure matrices. We used multivariable Cox regression. ' ' RESULTS ': 'The study included 25 292 persons. Compared to low occupational mechanical exposures and no pain, low mechanical exposures and combined pain showed an adjusted hazard ratio (HRadj) of 1.81 [95% confidence interval (95% CI) 1.58–2.08], while high mechanical exposures and combined pain showed HRadj 3.71 (95% CI 3.24–4.25) for sickness absence. The corresponding values for permanent work disability were 3.35 (95% CI 1.74–6.45) and 4.59 (95% CI 2.36–8.94). Job strain showed an association with sickness absence [HRadj 1.24 (95% CI 1.10–1.39)], while low social support was associated with both sickness absence and permanent work disability [HRadj 1.30 (95% CI 1.19–1.41) and 2.19 (95% CI 1.41–3.41), respectively]. ' ' CONCLUSIONS ': 'Combined pain in the upper and lower body was associated with sickness absence and permanent work disability, and high occupational mechanical exposures further increased the risk. Job strain showed a modest association with sickness absence, while low social support at work was associated with both outcomes, especially permanent work disability.
Keywords: cohort study; control; demand; force; job exposure matrix; lifting; lower-body pain; occupational exposure; occupational mechanical exposure; pain; permanent work disability; posture; psychosocial exposure; repetition; sickness absence; social support; upper-body pain; work disability